The role of institutionalization in the representation of G20 agenda-setting - Freites Hernández, Astrid (2022)
Reports affirm deficiencies in G20 governance evidencing under-representation of emerging economies in agenda-setting (Benson & Zürn 2019; Lei & Rui 2016; Prodi 2016). Underrepresentation is measured under the logic of an agenda that maximizes economic solutions based on the interests of developed countries. This has implications for emerging countries given that not all can achieve such maximization without first reducing economic vulnerabilities such as unemployment and social unprotection. This study explores the conditions that produce imbalance in the representation of G20 states' interests in their agenda-setting according to Krasner's (1999) theoretical approach. It argues that although the G20 has been institutionalizing its behavior over the last twelve years, it is still in the middle ground, leaving room for more developed nations with greater experience in international negotiations to set the agenda. Applying a qualitative methodology based on a sequential strategy of two data collection and analysis techniques, the results increase the understanding of how the level of institutionalization interacts with international policies. In the case of the G20, it is corroborated that on the road to greater institutionalization, emerging nations assume less prominence in agenda setting.